Baseline cartilage quality is associated with voxel‐based T1ρ and T2 following ACL reconstruction: A multicenter pilot study. Issue 3 (10th May 2016) - Russell, Colin; Pedoia, Valentina; Amano, Keiko; Potter, Hollis; Majumdar, Sharmila; ,
ABSTRACT: In this multi‐center study, voxel‐based relaxometry (VBR), a novel technique to automatically quantify localized cartilage change, was used to investigate T 1ρ and T 2 relaxation times of patients with anterior cruciate ligament (ACL) tears at the time of injury and 6 months after reconstructive surgery. Sixty‐four ACL‐injured patients from three sites underwent bilateral 3T MR T 1ρ and T 2 mapping; 56 patients returned 6 months after surgery. Cross‐sectional and longitudinal VBR comparisons of relaxation times were calculated. Noyes Score (NS) clinical grades of cartilage lesions were noted at both times and correlated with relaxation times. Lastly, patients were divided into two groups based on baseline NS grades in the injured knee. T 1ρ times of each group were assessed with VBR and compared. Results illustrate the feasibility of VBR for efficiently analyzing data from patients at different sites. Significant relaxation time elevations at baseline were observed in the injured knee compared to the uninjured, particularly in the posterolateral tibia (pLT). Longitudinally, a decrease was observed in the pLT and patella, while an increase was noted in the trochlea. Stratifying patients by baseline lesion presence revealed T 1ρ increased more 6 months after surgery in patients with lesions. Such findings propose that the presence of cartilage lesions at baseline are associated with the longitudinal progression of T 1ρ and T 2 after ACL injury, and may contribute to early cartilage degeneration. Furthermore, the speed and localized specificity of automatic VBR analysis may translate well for clinical application, as seen in this multicenter study. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:688–698, 2017.